Analysis Of Share Capital Gain Yield In Lq-45: Study Of Islam 212 Bela Action Events - Novi Puspitasari, Amelinda, Hari Sukarno (International Journal of Advanced Science and Technology, 2020)
This study aims to analyze changes in stock capital gains on the occurrence of the Islamic Defendant Actions 212 in 2016, 2017 and 2018. Analysis was carried out on 45 companies listing in the LQ-45 index divided by sectors. Tests using Paired Samples T-Test and Wilcoxon Test that depend on the results of normality test data. The test results show the differences in the average capital gain yield before and after the events of the Islamic Defendant Act 212 in 2017. Test results per sector also showed a change in the average capital gain in the Financial sector and the Consumer Goods Industry sector for the 212 year Defending Islamic Action 2017. Based on the results of the overall analysis, this study proves that the capital gain yields of the shares of companies listed on LQ-45 experienced changes in the occurrence of the Islamic Defendant Action 212 events in 2017.